Study Of Feasibility Of Meandg’s (Litsea Sp) Sawdust For The Removal Of Cadmium From Simulated Aqueous Solution - Muhammad Nazar; Ibnu Khaldun; Kana Puspita; . Habibati (Syiah Kuala University, 2015)
In this research, a series of batch laboratory experiments were conducted to examine the feasibility of Meandg’s (Litsea sp) saw dust for the removal of cadmium from simulated aqueous solution by using adsorption method. The research was carried out by studying the influence of pH of initial solution, contact time, adsorbent dosage, stirring speed, and the initial concentration of cadmium. The sawdust particle size used was 150 mesh and the experiments were conducted at room temperature of 27oC (±2oC). The residual concentration of cadmium from all batch experiments were analyzed using Atomic Adsorption Spectrophotometer (AAS) and each component equilibrium data was analyzed using Langmuir and Freundlich adsorption isotherms. The research findings shown that the optimum conditions are found to be at the pH of 6, the initial concentration of cadmium of 500 ppm with contact time of one hour, 3 gram of sawdust, and the optimum stirring at the speed of 350 rpm. The adsorption capacity of medang sawdust according to Langmuir and Freundlich isotherms are found respectively to be of 2.29 mg/g and 0.55 mg/g.